INTRINSIC REVIEW AND MISE-EN-SCÈNE STUDY OF GOOD WILL HUNTING MOVIE - Sri Purwati (Universitas Aki, 2021)
Mise-en-scène plays an important role to convey many things in a film or movie such as conveys message or moral value, build a narrative, etc. Based on those facts, this research tries to analyze the elements of mise-en-scène in Good Will Hunting movie, how mise-en-scène can work to communicate mood and meaning in Good Will Hunting Movie. The method used is qualitative. In the method of collecting data by doing observation data, document data, and audiovisual data that the primary data used the movie of Good Will Hunting. Analyze data based on its structural elements from movie, individual’s observation by observing movie and conducted the data analysis to describe mise-en-scène of the movie. The result of the research shows that applying of camera technique used in this movie is so many varieties. Long shot contains landscape but gives the viewers more specific idea of setting. A long shot may show the viewers the building where the action will be taken. Full shot contains a complete view of the characters. From this shot, viewers can take in the costumes of characters and may also help to demonstrate the relationships between characters. Close-up contains just one character’s face. This enables viewers to understand the actor's emotions and also allows them to feel empathy for the character. Overall the composition and cinematography techniques used in this movie are good.